Istikhdām al-Lugah al-‘Arabiyyah Ladā al-Aṭfāl zāwi al-Iḥtiyājāt al-Khāssah; ‘Alā Naẓri ‘Ilm al-Lugah al-Nafsī - Hasan, Laili Mas Ulliyah; Nurharini, Firdausi; Aziz, Muhammad Tareh (Study Program of Arabic Language Teaching, 2023)
This study aims to measure psychological gestures and language acuity (linguistics) from sensory integration barriers or disorders in a child with Down syndrome named Muhammad Syauqi, with an IQ below 45, a child with special needs from QIS Surabaya. The purpose of this study was to determine linguistic ability (language ability related to pronunciation sharpness, duration of memorizing Arabic vocabulary, and language regularity), psychological resilience in the process of speaking Arabic, and to identify pronunciation barriers that are owned by the cognitive abilities of children with Down syndrome IQ in below 45. This study uses qualitative research with observation methods, namely field observations, accompanied by analysis and distribution methods, namely listening, taking notes, changing, and replacing. The descriptive analysis method is used to present information and data. Data collection techniques were obtained through observation, interviews, and documentation. Data analysis used descriptive analysis by describing and summarizing the data obtained statistically. The analysis results show that language use in children with Down syndrome, namely Muhammad Syauqi, is very different because apart from the lower average IQ, obstacles to pronunciation acuity also occur due to physical disorders in the mouth to the throat. Down syndrome children can only say one word because of the lack of vocabulary. Children with Down syndrome will point to the object they want when asking for something. Children with Down syndrome have difficulty pronouncing the vowels /alif/, /fa'/, /syin/, /shod/, /hot/ /'ain/, and /groin/, as well as the vibration of the sound /ro'/. Children with Down syndrome also experience difficulties pronouncing the correct articulation, even sounds that sound unclear, and sometimes make faint sounds without meaning that cannot be understood.